Reconstruction of Islamic Family Education for the Interest in Reading and Writing the Qur'an for TPQ Children - Zulfikar Fikar; Nizam Alfarisy; Khoirul Harisin; ⁠Muhammad Imam Saputra; Jihan Kharisma Hidayatulloh (IQRO: Journal of Islamic Education, 2026)
This study examines the reconstruction of Islamic family education to strengthen TPQ children's interest in reading and writing the Qur'an in the digital era. Using a qualitative phenomenological approach, the research was conducted at TPQ Darul Fikri, Colomadu, Karanganyar, involving 27 participants consisting of teachers, parents, and students. Data were collected through observation, in-depth interviews, and documentation and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings indicate that limited parental involvement, weak religious role modeling, peer influence, excessive digital media use, and insufficient learning reinforcement contribute to the decline in children's Qur'anic literacy. To address these challenges, this study proposes a reconstruction model of Islamic family education that integrates Islamic parenting, parental role modeling, home-based Qur'anic learning routines, educational communication, positive reinforcement, and collaboration between parents and TPQ teachers. Theoretically, the study extends Social Learning Theory by demonstrating the interaction of observational learning, reinforcement, and self-efficacy within family education. Practically, the findings imply that families and TPQ institutions should establish structured learning routines and effective digital supervision to sustain children's motivation and participation in Qur'anic learning.